A new enemy in geriatric-gerontological care: socio-sanitarian implications imposed by COVID-19 in the aging population - Gutiérrez Murillo, Roberth Steven (Medicina Clínica y Social, 2021)
Letter to the Editor
Keywords: Letter to the Editor